Bohoslov’ja pislja Prosvitnyctva: miž morallju ta relihijeju (vid Danielja Defo do Martina Bubera) = Theology after Enlightenment: Between Moral and Religion (from Daniel Defoe to Martin Buber) - Panych, Oleksiy (Bogoslovskie razmyšlenija, 2018)
The article considers the questions of relations between religion and morality, how it appeared in the culture of European Enlightenment, and its further theological resonance. Already in the beginning of the 18th century the problem of relations between religion and morality was eloquently considered in Daniel Defoe’s "Robinson Crusoe". The main character of this novel, who happened to be alone at a desert island, first becomes a true Christian, and then tests his moral, and only later on also religious attitudes in communication with the local cannibal, meaningfully called "Friday". Voltaire in his L’Ingénu develops this problem further: his character, an Indian converted into Christianity, spontaneously arrives to all-rounded moral criticism of Christianity. Marquis de Sade in his La Philosophie dans le boudoir takes up this motive of all-rounded moral criticism of Christianity, but comes to much more radical conclusions: if a truly rational person necessarily will reach atheism, common people need religion in order to feel certain moral limits; however, this religion cannot be Christianity. Finally, Martin Buber’s works show how topical this problem, discovered by the Enlightenment, remains also in our contemporary culture - and, also, which peculiar difficulties and perspectives appear here in the theological dimension. To solve the problem, posed by the Enlightenment, Buber has to draw a distinction between religion and religiosity, and also postulate continuity of God’s revelation and dialogue between human being and God.